2012
DOI: 10.3346/jkms.2012.27.12.1591
|View full text |Cite
|
Sign up to set email alerts
|

Cauda Equina Syndrome Caused by Pseudogout Involving the Lumbar Intervertebral Disc

Abstract: Calcium pyrophosphate dihydrate (CPPD) deposition disease, also known as pseudogout, is a disease that causes inflammatory arthropathy in peripheral joints, however, symptomatic involvement of the intervertebral disc is uncommon. Herein, we describe a 59-yr-old patient who presented with cauda equina syndrome. Magnetic resonance imaging of the patient showed an epidural mass-like lesion at the disc space of L4-L5, which was compressing the thecal sac. Biopsy of the intervertebral disc and epidural mass-like le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 12 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…Pseudogout can deposit in the intervertebral disc, joint capsule, facet cysts, synovial cysts, and spaces within the neural foramen, causing compressive pathological presentations. [2][3][4][5][6][7] It has often been confused radiographically with calcified herniated disc, osteomyelitis/discitis with epidural phlegmon, or an extradural tumor. 5,6 Patients can also present with elevated inflammatory markers, further complicating the initial presentation differential diagnosis and perhaps placing bias on an infectious etiology, a much more common diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudogout can deposit in the intervertebral disc, joint capsule, facet cysts, synovial cysts, and spaces within the neural foramen, causing compressive pathological presentations. [2][3][4][5][6][7] It has often been confused radiographically with calcified herniated disc, osteomyelitis/discitis with epidural phlegmon, or an extradural tumor. 5,6 Patients can also present with elevated inflammatory markers, further complicating the initial presentation differential diagnosis and perhaps placing bias on an infectious etiology, a much more common diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a search of clinical articles, based on PubMed, since the year 2000, only a few case reports [ 5 , 7 , 8 , 10 , 12 , 13 ] of CPPD crystal deposition involving the lumbar spine were found. Specifically, only 2 case reports described acute CPPD crystal arthritis of the lumbar spine ( Table 1 ) [ 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…CPPD deposition disease commonly involves the major peripheral joints. Although CPPD deposition disease of the spine is less common, it can involve the ligamentum flavum; the longitudinal, supraspinous, and interspinous ligaments; the intervertebral discs; and the sacroiliac and apophyseal joint [2][3][4][5][6][7][8][9][10][11][12][13][14]. The definitive diagnosis of CPPD deposition disease is suspected on the basis of the clinical picture and radiographic/laboratory findings.…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, pseudogout can affect the spine; one autopsy study of more than 1,000 spinal specimens from patients with CPPD arthritis showed that crystals can accumulate in a variety of locations in the vertebral column, including the intervertebral disks, median atlantoaxial articulations, intraspinal and extraspinal ligaments, and apophyseal and sacroiliac joints . Pseudogout has also been known to present with mass‐like involvement of the spine that can be mistaken for tumors and has been reported as a cause of cauda equina syndrome . However, crystal‐induced arthritis after arthroplasty is rare, with only several dozen cases reported.…”
Section: Differential Diagnosismentioning
confidence: 99%